Homo Deus atau Deus Homo? Respons Teologi Kristen terhadap Narasi Posthumanisme - Obet Nego; Debby Christ Mondolu (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. This article examines the Homo Deus narrative popularized by Yuval Noah Harari and offers a Christian theological response through the contrast with Deus Homo. Harari envisions a future where technology enables humanity to overcome death, achieve happiness, and attain divinity. However, this narrative rests on the foundations of atheism, determinism, and hedonism, which exclude the spiritual dimension of humanity. Through a literature analysis, this article argues that Christian theology provides a more comprehensive alternative: God became human in Christ as the basis of salvation and human transformation. The incarnation, the cross, and the resurrection reject the illusions of posthumanism and affirm human dignity grounded in the imago Dei. Therefore, the future of humanity does not depend on technological achievements but on God’s promise of cosmic renewal.Abstrak. Artikel ini mengkaji narasi Homo Deus yang dipopulerkan Yuval Noah Harari serta memberikan respons teologis melalui kontras dengan konsep Deus Homo. Harari menawarkan visi masa depan manusia yang didorong oleh teknologi untuk menaklukkan kematian, meraih kebahagiaan, dan mencapai keilahian. Namun narasi tersebut dibangun di atas fondasi ateisme, determinisme, dan hedonisme yang menyingkirkan dimensi spiritual manusia. Melalui pendekatan analisis literatur, artikel ini menegaskan bahwa teologi Kristen menghadirkan alternatif yang lebih utuh: Allah menjadi manusia dalam Kristus sebagai dasar keselamatan dan transformasi manusia. Inkarnasi, salib, dan kebangkitan Kristus menolak ilusi posthumanisme dan meneguhkan martabat manusia berdasarkan imago Dei. Dengan demikian, masa depan manusia tidak terletak pada pencapaian teknologi, melainkan pada janji Allah yang memulihkan ciptaan.